PENDIDIKAN KESEHATAN MASYARAKAT DAN MANAJEMEN STRES DALAM MENSTABILKAN TEKANAN DARAH DAN KECEMASAN PENDERITA HIPERTENSI - Susila, Wahyu Dini Candra; Iswati, Iswati; Istifada, Rizkiyani; Susanti, Kamelia; Isya, Firda Nur; Ismawati, Ismawati (PPM STIKES Adi Husada, 2023)
Introduction & Aim: Hypertension is a condition where the systolic blood pressure is more than 140 mmHg and the diastolic is more than 90 mmHg. Hypertension data in East Java Province is ranked sixth in the 2018 Riskesdas. One of the various effects of hypertension is the anxiety and discomfort it causes. One of the non-pharmacological therapies that can be done is stress management in the form of deep breathing relaxation techniques and progressive muscle relaxation. Health education is given to increase participants' knowledge about the disease they are suffering from. Health education and stress management in the form of deep breathing and progressive muscle relaxation are offered to solve blood pressure and anxiety problems for people with hypertension. Method of Activity: Implementation of activities in the form of health education followed by demonstrations of the implementation of stress management in the form of deep breathing and progressive muscle relaxation. The activities were carried out en masse and the results were measured using the Hamilton Rating Scale for Anxiety (HRS-A) before the activity and 1 week after the activity. The activity was carried out on December 21 2022 in the Gundih Region, Bubutan, Surabaya City. Results: There was a decrease in blood pressure and a decrease in the participants' anxiety. Discussion: Stress management can help reduce blood pressure and anxiety scores, these conditions can be related because anxiety causes increased blood pressure, and it is necessary to increase knowledge with Health Education so that sufferers can have a better attitude towards their health problems.